2010
DOI: 10.3168/jds.2010-3336
|View full text |Cite
|
Sign up to set email alerts
|

Processing optimization of probiotic yogurt containing glucose oxidase using response surface methodology

Abstract: Exposure to oxygen may induce a lack of functionality of probiotic dairy foods because the anaerobic metabolism of probiotic bacteria compromises during storage the maintenance of their viability to provide benefits to consumer health. Glucose oxidase can constitute a potential alternative to increase the survival of probiotic bacteria in yogurt because it consumes the oxygen permeating to the inside of the pot during storage, thus making it possible to avoid the use of chemical additives. This research aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 49 publications
2
44
0
2
Order By: Relevance
“…These parameters include the fat level obtained by skimming the milk, the amount of milk powder added to standardize the total solids, the heat treatment of the milk, the inoculum level of starter culture and the stabilizer used (Mortazavian, Ehsani, Mousavi, Sohrabvandi, & Reinheimer, 2006;Mortazavian, Khosrokhavar, Rastegar, & Mortazaei, 2010;Peng, Horne, & Lucey, 2009;Soukoullis, Panagiotidis, Kourell, & Tzia, 2007). In the case of probiotic yogurts, there are additional parameters to be considered, such as the compounds used to supplement the milk (Lucas, Sodini, Monnet, Jolivet, & Corrieu, 2004), interaction between probiotic and starter cultures (Vinderola, Mocchiutti, & Reinheimer, 2002), the inoculation rate of the probiotic culture and its moment of addition during the yogurt processing (Kaur, Mishra, & Kumar, 2009), the quantity of water available during processing (Oliveira & Damin, 2003), oxygen level (Cruz et al, 2010;Cruz et al, 2012a,b) and the supplementation with a prebiotic ingredient (Oliveira, Perego, Oliveira, & Converti, 2009Debon et al, 2012).…”
Section: Analytical Resultsmentioning
confidence: 98%
“…These parameters include the fat level obtained by skimming the milk, the amount of milk powder added to standardize the total solids, the heat treatment of the milk, the inoculum level of starter culture and the stabilizer used (Mortazavian, Ehsani, Mousavi, Sohrabvandi, & Reinheimer, 2006;Mortazavian, Khosrokhavar, Rastegar, & Mortazaei, 2010;Peng, Horne, & Lucey, 2009;Soukoullis, Panagiotidis, Kourell, & Tzia, 2007). In the case of probiotic yogurts, there are additional parameters to be considered, such as the compounds used to supplement the milk (Lucas, Sodini, Monnet, Jolivet, & Corrieu, 2004), interaction between probiotic and starter cultures (Vinderola, Mocchiutti, & Reinheimer, 2002), the inoculation rate of the probiotic culture and its moment of addition during the yogurt processing (Kaur, Mishra, & Kumar, 2009), the quantity of water available during processing (Oliveira & Damin, 2003), oxygen level (Cruz et al, 2010;Cruz et al, 2012a,b) and the supplementation with a prebiotic ingredient (Oliveira, Perego, Oliveira, & Converti, 2009Debon et al, 2012).…”
Section: Analytical Resultsmentioning
confidence: 98%
“…Therefore, a visual evaluation of the models in order to choose the most adequate model is very important. However, due to its increased use in the area of studies involving shelf life and food stability (Cruz et al, 2010a), the Weibull distribution showed an adequate fit and was therefore chosen for the subsequent calculations. The estimates of maximum likelihood of the parameters of the Weibull distribution correspond to: Intercept (l) = 1.8787, and scale factor (r) = 0.7462.…”
Section: Survival Analysis Methodologymentioning
confidence: 99%
“…The prebiotic plain yogurt were processed according to Cruz et al (2010a) with some modifications. Oligofructose (Raftilose P95-BENEO, Orafti, Oreye, Bélgica) was added in the proportions 0%, 2%, 4%, 6% and 8% wt.…”
Section: Yogurt Processingmentioning
confidence: 99%
“…Although some researchers still use the 'one-factor -at-a-time' approach to develop new products, the use of experimental design in the development of fortified foods has increased because it facilitates the investigation of the interaction between the effects of variables through mathematical models and response surface methodology. This statistical technique has been used to study the effects of orange pomace in the production of gluten-free bread (O'Shea et al, 2015), in the acceptance of a prebiotic beverage made with cashew nut and passion fruit juice (Rebouças et al, 2014), in the development of cookies enriched with added guava peel (Bertagnolli et al, 2014), and in the optimization of probiotic yogurts (Cruz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%